Effective Biosorption of Nickel(II) from Aqueous Solutions Using Trichoderma viride. (31st October 2012) - Sujatha, P.; Kalarani, V.; Kumar, B. Naresh
Abstract : The primary objective of the present study is to evaluate the optimization conditions such as kinetic and equilibrium isotherm models involved in the removal of Ni(II) from the aqueous solutions by Trichoderma viride . The biosorbent was characterized by FTIR and SEM. The optimum biosorption conditions were determined as a function of pH, biomass dosage, contact time, initial metal ion concentration, and temperature. The maximum Ni(II) biosorption was obtained at pH 4.5. The equilibrium data were better fit by the Langmuir isotherm model than by the Freundlich isotherm. The kinetic studies indicate that the biosorption process of the metal ion Ni(II) has followed well the pseudo-second-order model. The sum of the square errors (SSE) and chi-square (χ 2 ) tests were also carried out to find the best fit kinetic model and adsorption isotherm. The maximum biosorption capacity (q m ) of T . viride biomass was found to be 47.6 mg/g for Ni(II) ion. Therefore, it can be concluded that T . viride biomass was effective and low-cost potential adsorbent to remove the toxic metal Ni(II) from aqueous solutions. The recovery process of Ni(II) from T . viride biomass was found to be higher than 98% by using 0.25 M HNO3 . Besides the application of removal of toxic metal Ni(II) from aqueous solutions, the biosorbent T . viride can be reused for five consecutive sorption-desorption cycles was determined.